HIV Transmission Rates and Factors Associated with Recent HIV Infection: Results from the Ndhiwa HIV Impact Assessment, South Nyanza, Kenya, 2012. (4th October 2017) - Agyemang, Elfriede; Zeh, Clement; Mukui, Irene; Maman, David; Kim, Andrea
Abstract: Background: Identifying populations with high HIV transmission rates is important for prevention and treatment strategies. Persons with recently acquired HIV infection are drivers of HIV transmission due to high levels of HIV viral load (VL). We assessed annual HIV transmission rates and factors associated with recent infection to inform targeted interventions in a hyperendemic region in Kenya. Methods: The Ndhiwa HIV impact assessment was a population-based survey among persons aged 15–59 years living in South Nyanza, Kenya in 2012. Respondents were tested for HIV using rapid tests per national guidelines and provided blood for centralized testing. Specimens from HIV+ persons were tested for VL and recent infection. Recent infection was defined as normalized optical density value <1.5 on the Limiting Antigen Enzyme Immunoassay, VL >1, 000 copies/mL, and no report of HIV treatment. The annual HIV transmission rate per 100 persons living with HIV (PLHIV) was calculated as HIV incidence divided by HIV prevalence, multiplied by 100. Annualized HIV incidence was estimated, assuming a mean duration of recent infection of 141 days (confidence interval [CI] 123–160). Multivariate analysis identified independent factors associated with recent infection. Estimates were adjusted for survey design. Results: Of 6, 076 persons tested, 1, 457 were HIV+, and 28 were recently infected. HIV incidence and prevalence were 1.7% (CI 1.5–2.0) and 24.1% (CI 22.6–25.5), respectively. Per 100 PLHIV, the annual HIV transmission rate was 7.0 and varied by sex (4.6 male vs. 8.3 female), age (5.2 aged 30+ vs. 10.4 aged <30), and residence (1.4 Kobama vs. 12.0 Riana vs. 12.1 Pala divisions). After controlling for age, sex, and residence, recently infected persons were significantly more likely to reside in Pala division (AOR 8.3, CI 1.1–62.9) than HIV-uninfected persons. Conclusion: Approximately 7 in 100 PLHIV transmitted to HIV-uninfected persons in South Nyanza in 2012, similar to national rates observed in the 2012 Kenya AIDS Indicator Survey. HIV transmission rates were higher in females than males, younger than older, and Riana and Pala than other divisions. Residence in Pala was a risk factor for recent infection. These findings could guide prioritization of interventions to interrupt HIV transmission in this hyperendemic setting. Disclosures: All authors: No reported disclosures.